2013
DOI: 10.1073/pnas.1321305110
|View full text |Cite
|
Sign up to set email alerts
|

Argininosuccinate synthetase 1 depletion produces a metabolic state conducive to herpes simplex virus 1 infection

Abstract: Herpes simplex virus 1 (HSV-1) infection triggers specific metabolic changes in its host cell. To explore the interactions between cellular metabolism and HSV-1 infection, we performed an siRNA screen of cellular metabolic genes, measuring their effect on viral replication. The screen identified multiple enzymes predicted to influence HSV-1 replication, including argininosuccinate synthetase 1 (AS1), which consumes aspartate as part of de novo arginine synthesis. Knockdown of AS1 robustly enhanced viral genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 47 publications
(36 reference statements)
0
39
0
1
Order By: Relevance
“…The HSV-1 and HCMV infection metabolomes were also studied in the context of siRNA knockdown screening of cellular enzymes by Grady et al, 118 who identified the argininosuccinate synthase 1 (AS1) as a single key metabolic enzyme whose down-regulation mimics an HSV-1 infection state. Contrarily to HSV-1 infection, AS1 knockdown cells decreased HCMV infection, emphasizing the disparity between the modes of action of these two viruses on host cell metabolism.…”
Section: Metabolomicsmentioning
confidence: 99%
“…The HSV-1 and HCMV infection metabolomes were also studied in the context of siRNA knockdown screening of cellular enzymes by Grady et al, 118 who identified the argininosuccinate synthase 1 (AS1) as a single key metabolic enzyme whose down-regulation mimics an HSV-1 infection state. Contrarily to HSV-1 infection, AS1 knockdown cells decreased HCMV infection, emphasizing the disparity between the modes of action of these two viruses on host cell metabolism.…”
Section: Metabolomicsmentioning
confidence: 99%
“…HCMV infected cells showed enhanced glycolytic flux and TCA cycle to fuel fatty acid biosynthesis (68). Furthermore, reducing the expression of a single metabolic enzyme, argininosuccinate synthetase (AS1), was sufficient to mimic these HSV-1 induced metabolomic changes to improve viral replication (69). These metabolomic approaches can point to potential new sites for antiviral therapy (70).…”
Section: Metabolomic Approaches To Define and Map Biochemical Pathwaysmentioning
confidence: 99%
“…Grady et al used an siRNA screen to show that argininosuccinate synthase 1 (ASS1) knockdown increased virus yield and subsequently used metabolomic profiling to show that ASS1 inactivation resulted in a metabolic signature that closely resembled HSV-1 infection, in which levels of aspartate, carbamoyl-aspartate, one of the first committed metabolites on the pathway to nucleotide synthesis, and nucleotides and their precursors were reduced (Grady et al, 2013). …”
Section: Metabolomics To Reveal Unique and Novel Roles For Previouslymentioning
confidence: 99%